Changes in leaf functional traits of Houttuynia cordata in response to soil environmental factors in Anqing city of Anhui Province in China. Issue 1 (1st January 2019) - Wang, Xiaopeng; Ye, Meirong; Zhang, Xueping; Xu, Rusong; Xu, Dongqing
ABSTRACT: Plant functional traits reflect the responses and adaptations of plants to their immediate environment. In this study, 10 different sources of the Houttuynia cordata population in Anhui Province, China, were examined in terms of their leaf responses and adaptive mechanisms towards soil characteristics. Our study observed the leaf weight ratio depicted a significant negative correlation with leaf potassium content (r=-0.652, P < 0.05) and an extremely significant negative correlation with leaf saturated water content (r=-0.720, P < 0.01) in different H. cordata populations. The leaf mass per area, leaf weight ratio, leaf nitrogen content, leaf potassium content, and leaf saturated water content in H. cordatas showed a significant correlation with soil available phosphorus, available potassium, soil total porosity, soil volume weight, and pH. Lastly, a significant relationship between leaf potassium content in plants and soil volume weight was observed (R 2 =0.448, P < 0.01).